An investigation on the effect of street morphology to ambient air quality using six real-world cases. (September 2017) - Shen, Jialei; Gao, Zhi; Ding, Wowo; Yu, Ying
Abstract: Street canyons are vulnerable to air pollution mainly caused by vehicle emissions, which are therefore closely related to pedestrians' health. Previous studies have showed that air quality in street canyons is associated with street morphology, though the majority of them have focused on idealized street models. This paper attempts to investigate the relationship of street morphology to air quality for 6 irregular real-world cases selected from America, Europe, and China, i.e. Manhattan, Paris, Barcelona, Berlin, London and Nanjing. Each street is analyzed as a set of slices to propose a couple of morphology indices for quantitatively assessing the actual street morphology. Pollutant transport rate of mean flows and turbulent diffusion, net escape velocity and age of air are obtained from computational fluid dynamics (CFD) simulations to assess the ventilations and pollutant dispersion within street canyons with a parallel approaching wind. The results show that the street morphology characteristics, including the street width, lateral openings and intersections, are closely related to the air flows in street canyons. The air quality improves with a decreasing aspect ratio of central street owing to a larger vertical exchange through the street roof, which suggests an open central street is of better air quality. The lateral openings and intersections of streets have important effects on the air flows in street canyons, and the effects are particularly pronounced when the street widths are similar. The street continuity ratio indicates street continuity. It relates to the openings and the symmetry of a street and impacts on the air flows and pollutant dispersion through the lateral openings of the central street. The street spatial closure ratio is determined by the street continuity ratio and the aspect ratio of the central street. When the aspect ratio of central street is not excessively high, higher values of street continuity ratio and spatial closure ratio can lead to a stronger channel flow in street canyons and improve the air quality. The octagon intersections are favorable for air flowing through the lateral openings and improve the channel flows. The oblique intersections can also greatly improve the street ventilations, mainly due to the enhanced air flows through the lateral openings and the increased turbulent diffusion through the street roofs. Highlights: Relationship of street morphology and air quality for 6 real-world cases is analyzed. Street continuity ratio and other indices are proposed to quantify street morphology. Air quality improved with a decreasing aspect ratio due to larger vertical exchange. Higher street continuity and spatial closure lead to a stronger channel flow. Octagon and oblique intersections are favorable for central street ventilation.